2014
DOI: 10.1186/gb-2014-15-1-r14
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the expression landscape of RNA-binding proteins in human cancers

Abstract: BackgroundRNA-binding proteins (RBPs) play important roles in cellular homeostasis by controlling gene expression at the post-transcriptional level.ResultsWe explore the expression of more than 800 RBPs in sixteen healthy human tissues and their patterns of dysregulation in cancer genomes from The Cancer Genome Atlas project. We show that genes encoding RBPs are consistently and significantly highly expressed compared with other classes of genes, including those encoding regulatory components such as transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
215
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(226 citation statements)
references
References 74 publications
11
215
0
Order By: Relevance
“…We found that the RNAbinding ability of LARP4B contributed to its growth-inhibitory function, indicating that LARP4B suppresses glioma cell growth through an interaction with RNA. Deregulated expression of RNAbinding proteins is commonly observed in cancer (38), and emerging evidence indicates causative roles for the dysregulation of RNA-binding proteins in cancer progression (39). Alternative splicing of mRNA precursors (pre-mRNA) is one of the mechanisms through which dysregulation of RNA-binding proteins confers growth advantage to cancer cells, because cancer cells favor the production of protein isoforms that promote growth and survival (17,40).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the RNAbinding ability of LARP4B contributed to its growth-inhibitory function, indicating that LARP4B suppresses glioma cell growth through an interaction with RNA. Deregulated expression of RNAbinding proteins is commonly observed in cancer (38), and emerging evidence indicates causative roles for the dysregulation of RNA-binding proteins in cancer progression (39). Alternative splicing of mRNA precursors (pre-mRNA) is one of the mechanisms through which dysregulation of RNA-binding proteins confers growth advantage to cancer cells, because cancer cells favor the production of protein isoforms that promote growth and survival (17,40).…”
Section: Discussionmentioning
confidence: 99%
“…One of the pivotal players that are responsible for post-transcriptional regulatory control in eukaryotic organisms are the RNA binding proteins (RBPs). RBPs bind single or double stranded RNA and determine their fate from synthesis to decay [1][2][3][4][5]. They possess one or more domains that can recognize RNA in a sequence specific manner and hence conferring different binding affinities and specificities.…”
Section: Introductionmentioning
confidence: 99%
“…When bound to an mRNA, these proteins control all the major steps of an mRNA's life, including splicing, export, localization, translation and degradation [1,3,4]. Due to their multi-functionality, RBPs become the most prominent of the post transcriptional machinery and any alteration in their function can cause deleterious effects which could lead to numerous complex disorders [2,7,8]. Hence, it becomes important to understand the structural and functional characteristics of RBPs in humans.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms are altered in several diseases, including cancer, and this could be due to an aberrant expression and activity of RNA-binding proteins (RBPs) (2,3). These proteins are key regulators of post-transcriptional gene expression and among them, one the most known RBP to be implicated in tumorigenesis is Hu antigen R (HuR) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%